WOMEN ENTREPRENEURS IN MEXICO: AN ANALYSIS OF FINANCIAL, HUMAN AND SOCIAL CAPITAL - Paola Isabel Rodriguez-Gutierrez; María del Mar Fuentes-Fuentes; Lazaro Rodriguez-Ariza (European Scientific Journal, ESJ, 2013)
It has been stated that entrepreneurship represents an important force in the economies. Particularly, women entrepreneurs constitute a sector in growth towards which many organisms as well as the academic area have overturned the attention. The main objective of this research is to detect the presence of a selected group of capabilities and resources in women-owned business in Mexico. Their possible interrelationship was evaluated utilizing the tool analysis of variance (ANOVA).This research adopts the Resource Based View of the firm as theoretical framework, considering in its analysis three strategic capabilities and three important resources. The data used for this analysis was obtained from two women associations in México. Results show that human and social capital may be important for the appropriate display of some capabilities, which may have significant implications for management. According to the analysis made, women entrepreneurs should pay special attention to the capabilities and resources examined.